Manajemen Pembelajaran Metode Bil Qolam dalam Meningkatkan Kemampuan Membaca Al-Qur’an - soraya aisyah; Istikomah (Mu'allim, 2025)
The purpose of this study is to describe the Learning Management of Bil Qolam Method in Improving Students' Al-Qur'an Reading Ability at SMP Plus Sabilur Rosyad. This study puts forward the elements of planning, organizing, implementing, supervising, and evaluating. The approach applied in this study is descriptive qualitative. Data were collected through observations and interviews, then analyzed through the stages of data condensation, data presentation, and conclusion drawing. The research findings revealed that in the planning management of the Bil Qolam method at SMP Plus Sabilur Rosyad, the teacher had prepared a Teaching Program Plan and an assessment sheet. In the organizing stage, the teacher conducts the process of grouping students based on their respective abilities to determine the level of the volume by conducting a reading test of the Qur'an. At the implementation stage, the Bil Qolam method begins with greetings, learning activities, closing prayers. At the supervision stage, the Bil Qolam coordinator is in charge of leading the success of the learning management process and getting support from the principal as the person in charge. In the evaluation stage, the Bil Qolam method is obtained from the assessment results every week which are then recapitulated. The management of the Bil Qolam method has been implemented quite well and can improve students' ability to read the Qur'an. Although there are still a few obstacles faced, namely teachers need to improve teaching competence and lack of time allocation.